ANALISIS FAKTOR YANG MEMENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM SONGKET SIPIROK DI KABUPATEN TAPSEL - Muhmmad Wandisyah R. Hutagalung; Ella Zefriani; Syarifah Isnaini; Hikmah Nasution (Jaksya: Jurnal Akuntansi Syariah, 2023)
This study aimed to obtain evidence on the effect of educational background, level of education, business scale, and long efforts to use accounting information on SMEs in Sragen. The population in this study is SMEs that are in Sragen. Convinience sampling technique using a sampling of 100 people with a margin of error of 5%. Data collected by distributing questionnaires to business owners of SMEs. Analyzed the data before it has been tested for validity and reliability. Data were analyzed using logistic regression. The results showed that the value of Hosmer and Lemeshow's Goodness of Fit test is equal to 0.281. Value of 0.281 is greater than 0.05, it can be concluded the model is acceptable. R² Negelkerke's value is 0.911, which means the dependent variable can be explained by the independent variables of 91.1% and the remaining 8.9% is explained by other variables. Results of the testing variables using logistic regression result is a variable level of education has a significant value 0.344 thus does not affect the use of accounting information. Educational background variables have a significant value 0.866 thus does not affect the use of accounting information. Variable business scale has significant value 0,005 that affect the use of accounting information. Variable long the business has significant value 0,018 that affect the use of accounting information.